Efficacy and safety of intravenous recombinant tissue plasminogen activator in mild ischaemic stroke: a meta-analysis. Issue 1 (5th January 2018) - You, Shoujiang; Saxena, Anubhav; Wang, Xia; Tan, WeeYong; Han, Qiao; Cao, Yongjun; Liu, Chun-Feng
Abstract : The benefits and safety of intravenous recombinant tissue plasminogen activator (IV-tPA) for patients with mild ischaemic stroke (MIS) are still unclear. The objective of this meta-analysis was to evaluate the efficacy and safety of IV-tPA as treatment for patients with MIS. We performed a systematic literature search across MEDLINE, Embase, Central, Global Health and Cumulative Index to Nursing and Allied Health Literature (CINAHL), from inception to 10 November 2016, to identify all related studies. Where possible, data were pooled for meta-analysis with odds ratio (OR) and corresponding 95% confidence interval (CI) using the fixed-effects model. MIS was defined as having National Institutes of Health Stroke Scale score of ≤6. We included seven studies with a total of 1591 patients based on the prespecified inclusion and exclusion criteria. The meta-analysis indicated a high odds of excellent functional outcome based on the modified Rankin Scale or Oxfordshire Handicap Score 0–1 (OR=1.43; 95% CI 1.14 to 1.79; P=0.002, I 2 =35%) in patients treated with IV-tPA compared with those not treated with IV-tPA (74.8% vs 67.6%). There was a high risk of symptomatic intracranial haemorrhage (sICH) with IV-tPA treatment (OR=10.13; 95% CI 1.93 to 53.02; P=0.006, I 2 =0%) (1.9% vs 0.0%) but not mortality (OR=0.78; 95% CI 0.43 to 1.43; P=0.43, I 2 =0%) (2.4% vs 2.9%). Treatment with IV-tPA was associated with better functional outcome but not mortality among patients with MIS, although there was an increased risk of sICH. Randomised trials are warranted to confirm these findings.